1997
DOI: 10.1007/s002130050304
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine discrimination and self-administration in humans as a function of smoking status

Abstract: Nicotine's discriminative stimulus effects may be critical to understanding reinforcement of tobacco smoking. It is not known whether regular nicotine exposure produces tolerance or sensitivity to these effects. In this study, male and female smokers (n = 11) and never-smokers (n = 10) were trained to discriminate 20 micrograms/kg nicotine by nasal spray from placebo (0) on day 1. On day 2, both groups were tested on generalization of this discrimination across intermittent presentations of 0, 3, 6, 12, and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 34 publications
3
65
1
Order By: Relevance
“…If carry-over effects were a significant factor, then dose-response functions would have been attenuated; however, we observed orderly dose-related changes on many variables. This study builds on previous research in behavioral pharmacology using cumulative or repeated dosing paradigms to determine dose-response functions within single experimental sessions (Chait et al, 1988;Perkins et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…If carry-over effects were a significant factor, then dose-response functions would have been attenuated; however, we observed orderly dose-related changes on many variables. This study builds on previous research in behavioral pharmacology using cumulative or repeated dosing paradigms to determine dose-response functions within single experimental sessions (Chait et al, 1988;Perkins et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A key to determining nicotine's reinforcing efficacy in humans may lie in greater knowledge of these relatively subtle interoceptive and subjective effects (Henningfield et al 1985;Stolerman and Jarvis 1995). We have found that smokers can learn to discriminate nicotine by nasal spray (Perkins et al 1994a(Perkins et al , 1996 and may develop tolerance to the interoceptive and reinforcing effects of higher nicotine doses (Perkins et al 1997).…”
Section: Introductionmentioning
confidence: 97%
“…USDHHS 1988;Perkins et al 1997). A key to determining nicotine's reinforcing efficacy in humans may lie in greater knowledge of these relatively subtle interoceptive and subjective effects (Henningfield et al 1985;Stolerman and Jarvis 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Human laboratory paradigms have been used to investigate various nicotine dependence phenomena such as nicotine discrimination (Perkins et al, 1997;Perkins et al, 1999), nicotine reinforcement (Perkins et al, 2001), deprivation effects (Hatsukami et al, 1984), self-administration behavior (Hatsukami et al, 1998;Perkins et al, 1997), and cue reactivity (Carter & Tiffany, 1999 for review). Researchers have also examined a human analogue of reinstatement as a model of smoking relapse, which involves a non-contingent cigarette exposure after a period of abstinence (Chornock et al, 1992;Juliano & Stitzer, 2003;King & Meyer, 2000).…”
mentioning
confidence: 99%